ANALISA PERUBAHAN DESIGN PONDASI BAWAH ABUTMENT-1 JEMBATAN KIKUBA PULAU ENGGANO DARI PONDASI SUMURAN MENJADI PONDASI BORE PILE - M.Arif Rahman.S Arif; Nilda Tri Putri (Universitas Bengkulu, 2024)
Foundation is a structural element that functions as a support for the construction loads above it. These loads are transmitted to the soil, so the depth of the foundation must reach the depth of hard soil; therefore, the determination of the depth and type of foundation used must be based on soil investigation conducted during the bridge construction planning phase. The Kikuba bridge project is planned to use pile foundations with a depth of 5 meters. After conducting soil investigation using drilling equipment, the N-SPT 60 results for Abutment-1 were obtained at an average depth of 19 meters, rendering pile foundations unsuitable. The accuracy of selecting the type of foundation used depends greatly on the depth of hard soil. The Kikuba bridge construction project encountered an average depth of hard soil at 19 meters, thus necessitating an analysis to change the design from pile foundations to bore pile foundations, while meeting the technical requirements of the foundation and analyzing using the Meyerhoof method.